INNOVATION, DIGITAL TECHNOLOGIES, AND POST-COVID-19 WORK AND STUDY TRENDS IN THE ASIA PACIFIC REGION - Blount, Yvette (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Working from anywhere (telework, remote work, work from home) has been an area of research and discussion for decades. During COVID-19, the worldwide health mandates for working from home refocused the debate about the future of work, particularly the location of work. Some benefits include more flexibility and autonomy, less commuting time and better work/life balance. The challenges include social and professional isolation, limitations for collaboration and increasingly invasive use of technology to monitor workers. COVID-19-mandated work from home has shown that workers can be productive working remotely. It has also reignited the discussion about the location of work and the future of work. There is no consensus. However, hybrid work, where workers work some of the time at home, is becoming more common. The higher education sector is an example of a workplace where a key stakeholder, the student, is driving how they want to interact, for example, not attending in-person classes. Collaboration and social connections are more important than ever to foster innovation and a sense of belonging, referred to as the hybrid paradox. The future of work is uncertain; however, workers will likely demand more flexibility about where they work.